The effect of disorder of small spheres on the photonic properties of the inverse binary NaCl-like structure. (17th August 2017) - Pattabhiraman, Harini; Dijkstra, Marjolein
Abstract: Inverse opal structures are experimentally realisable photonic band gap materials. They suffer from the drawback of possessing band gaps that are extremely susceptible to structural disorders. A binary colloidal NaCl lattice, which is also experimentally realisable, is a promising alternative to these opals. In this work, we systematically analyse the effect of structural disorder of the small spheres on the photonic properties of an inverse binary NaCl lattice with a size ratio of 0.30 between the small and large spheres. The types of structural disorders studied include the position of the small spheres in the octahedral void of the large spheres, polydispersity in size of the small spheres, and the fraction of small spheres in the crystal. We find a low susceptibility of the band gap of the inverse NaCl lattice to the disorder of the small spheres.